Methodological perspective of evaluation of Green public procurement - Pelsa, Inese; Balina, Signe (University of Latvia, 2020)
Every year the European Union (EU) Member States collectively spend around 14% of Gross Domestic Product (GDP) on public procurement. In Latvia, public procurement accounts for 17% of GDP. The review of the new public procurement directives and their transposition process in Latvia plans to show new opportunities for green public procurement (GPP) application: the contracting authority will be able to reject, for example, an abnormally low bid, include environmental management system requirements in the selection criteria, use life cycle costing criteria, etc. GPP is the systematic integration of environmental criteria into all activities related to the procurement of goods or services, from the identification of needs, the development of appropriate specifications and evaluation procedures, to the monitoring of the results achieved. Solutions for the promotion of GPP proposed by the new Public procurement Law project and the Cabinet of Ministers' draft regulation "Requirements and Application of Green Public Procurement" will also be analyzed. The aim of the work is to explore the application of GPP to improve the quality of GPP.
Keywords: Green public procurement; procurement; Research Subject Categories::SOCIAL SCIENCES::Business and economics